Superficial cephalic myology of Mesotes strigatus (Günther, 1858) (Serpentes: Dipsadidae) - Ferreira, Ana Beatriz Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Morphological studies are very relevant in the context of phylogenetic relationships, being even more relevant for groups that show a high level of polymorphism and taxonomic complexity, which is the case for the Tachymenini tribe (Serpentes: Dipsadidae). Molecular studies have already been done for this tribe, including the subject of study Mesotes strigatus, but descriptive morphological information for this group is still scarce. To help bridge this gap, three different specimens were dissected and the cephalic muscles were described regarding their shapes and sizes. Six distinct muscles were described including the Levator Anguli Oris (LAO), M. adductor mandibulae externus medialis (MAMEM), M. adductor mandibulae externus superficialis (MAMES), M. depressor mandibulae (DM), M. neurocostomandibularis (NCM) and Musculus Pterygoideus (PG), as well as three glands, the Duvernoy’s glands (DVG), Supralabial glands (SLG) and Infralabial Glands (ILG).The description of the superficial myology in M. strigatus follows the phylogenetic pattern conserved in this group, showing consistency with other Dipsadidae. These data provide anatomical evidence supporting the phylogenetic placement of M. strigatus and establish a foundation for future comparative studies within Tachymenini.

Estudos morfológicos são muito relevantes no contexto das relações filogenéticas, sendo ainda mais relevantes para grupos que apresentam um alto nível de polimorfismo e complexidade taxonômica, como é o caso da tribo Tachymenini (Serpentes: Dipsadidae). Estudos moleculares já foram realizados para essa tribo, incluindo o objeto de estudo Mesotes strigatus, mas informações morfológicas descritivas para esse grupo ainda são escassas. Para ajudar a preencher essa lacuna, três diferentes espécimes foram dissecados e os músculos cefálicos foram descritos quanto às suas formas e tamanhos. Seis músculos distintos foram descritos, incluindo o Levator Anguli Oris (LAO), M. adductor mandibulae externus medialis (MAMEM), M. adductor mandibulae externus superficialis (MAMES), M. depressor mandibulae (DM), M. neurocostomandibularis (NCM) e Musculus Pterygoideus (PG), assim como três glândulas: glândula de Duvernoy (DVG), glândulas supralabiais (SLG) e glândulas infralabiais (ILG). A descrição da miologia superficial em M. strigatus segue o padrão filogenético conservado neste grupo, mostrando consistência com outros Dipsadidae. Esses dados fornecem evidências anatômicas que sustentam a posição filogenética de M. strigatus e estabelecem uma base para futuros estudos comparativos dentro de Tachymenini.
Miologia cefálica superficial de Mesotes strigatus (Günther, 1858) (Serpentes: Dipsadidae)
Keywords: Cobras; Morfologia (Biologia); Músculos; Filogenia